2013
DOI: 10.1002/jat.2902
|View full text |Cite
|
Sign up to set email alerts
|

Phthalates efficiently bind to human peroxisome proliferator activated receptor and retinoid X receptor α, β, γ subtypes: an in silico approach

Abstract: This exhaustive in silico study looks into the molecular interactions of phthalates and their metabolites with human peroxisome proliferator-activated receptor (hPPAR) and retinoid X receptor (hRXR) α, β and γ subtypes--the nuclear receptor proteins function as transcription factors by regulating the expression of downstream genes. Apart from the much discussed plasticizer bisphenol A, we examined the binding affinities of 15 common diphthalates and their monophthalates, natural (linoleic acid, conjugated lino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 32 publications
3
38
0
Order By: Relevance
“…This finding is not surprising because previous studies have demonstrated that other EDCs with putative obesogenic properties such as tributyltin (TBT), 6 bisphenol A (BPA), and DEHP 57 can activate the PPAR−RXR heterodimeric complex primarily through their interaction with RXR. 55,20 Overall, the potential binding of DiDP to each partner (i.e., PPAR and RXR) of the heterodimer can result in deregulated PPAR-RXR signaling pathways, which have been already observed following DEHP exposure. 56 Gene Expression Profile of DiDP-Treated Sea Bream Hepatocytes.…”
Section: ■ Experimental Proceduresmentioning
confidence: 96%
“…This finding is not surprising because previous studies have demonstrated that other EDCs with putative obesogenic properties such as tributyltin (TBT), 6 bisphenol A (BPA), and DEHP 57 can activate the PPAR−RXR heterodimeric complex primarily through their interaction with RXR. 55,20 Overall, the potential binding of DiDP to each partner (i.e., PPAR and RXR) of the heterodimer can result in deregulated PPAR-RXR signaling pathways, which have been already observed following DEHP exposure. 56 Gene Expression Profile of DiDP-Treated Sea Bream Hepatocytes.…”
Section: ■ Experimental Proceduresmentioning
confidence: 96%
“…[35] Several phthalates have been shown to be PPARγ activators, causing obesogenic effects. [34-37] PPARs form heterodimers with the retinoid X receptors (RXRs), binding together on the target DNA and thereby activating the expression of downstream genes. Therefore, RXRs have the same targets as PPARs.…”
Section: Potential Mechanisms Of Effectmentioning
confidence: 99%
“…Many common phthalates have been shown to bind to RXRs. [37] Likewise, oxidative stress is a potential mechanism for phthalate effects. In a prospective cohort study of pregnant women all urinary phthalates were associated with increased oxidative stress markers.…”
Section: Potential Mechanisms Of Effectmentioning
confidence: 99%
See 2 more Smart Citations